On the Use of Autonomous Sailboats as Learning Tools in Computer Science and Engineering Undergraduate Courses - Gonçalves, Luiz M. G.; Garcia, Luciane T. S.; Negreiros, Alvaro P. F.; Santos, Davi H. Dos; Brandão, Diego N.; Guerra, Raphael; Clua, Esteban W. G. (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS); 2023: Anais do XV Simpósio Brasileiro de Robótica e XX Simpósio Latino Americano de Robótica, 2023)
We introduce a study about the possibility of using currently developed sailboat robots as tools for motivating learning skills by undergraduate students, including programming abilities, among other disciplines. By way of a survey done with several (former) undergraduate students that worked on autonomous sailboat projects in two different institutions, we demonstrate that it can be an interesting learning resource. These students used it both as a final course project or even only as project participants. Ultimately, we figured out that the platforms can be used as supporting artifacts for Problem-Based Learning in several disciplines. Their use could be restricted due to the space necessary. However, smaller versions have been pointed out as a solution. Another positive point is the motivation that it gives to the students.